2010
DOI: 10.1002/pmic.201000348
|View full text |Cite
|
Sign up to set email alerts
|

Proteome mining for novel IgE‐binding proteins from the German cockroach (Blattella germanica) and allergen profiling of patients

Abstract: Although cockroaches are known to produce allergens that can cause IgE-mediated hypersensitivity reactions, including perennial rhinitis and asthma, the various cockroach allergens have not yet been fully studied. Many proteins from the German cockroach show high IgE reactivity, but have never been comprehensively characterized. To identify these potential allergens, proteins were separated by 2-DE and IgE-binding proteins were analyzed by nanoLC-MS/MS or N-terminal sequencing analysis. Using a combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 51 publications
2
54
0
3
Order By: Relevance
“…Prevalence of IgE antibodies was highest for rBla g 2 (54.4%) and rBla g 5 (37.4%) among the 118 sera analyzed; however, patterns of IgE antibody binding were unique to each subject. More recently, Chuang et al [6 ]also showed that IgE reactivity profiles were heterogeneous, in a group of 32 cockroach-allergic patients presumably from Taiwan. Using a panel of recombinant cockroach allergens Bla g 1, Bla g 2, Bla g 4, Bla g 5, Bla g 7, the newly identified B. germanica enolase, arginine kinase and vitellogenin, the authors demonstrated substantial differences in the prevalence of IgE reactivity to each of the allergens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence of IgE antibodies was highest for rBla g 2 (54.4%) and rBla g 5 (37.4%) among the 118 sera analyzed; however, patterns of IgE antibody binding were unique to each subject. More recently, Chuang et al [6 ]also showed that IgE reactivity profiles were heterogeneous, in a group of 32 cockroach-allergic patients presumably from Taiwan. Using a panel of recombinant cockroach allergens Bla g 1, Bla g 2, Bla g 4, Bla g 5, Bla g 7, the newly identified B. germanica enolase, arginine kinase and vitellogenin, the authors demonstrated substantial differences in the prevalence of IgE reactivity to each of the allergens.…”
Section: Discussionmentioning
confidence: 99%
“…Cockroach allergens comprise at least 10 groups of distinct proteins, including Bla g 1 and Per a 1 (midgut microvilli protein homologues), Bla g 2 and Per a 2 (inactive aspartic proteases), Per a 3 (arylphorin/hemocyanin), Bla g 4 and Per a 4 (male pheromone transport lipocalins), Bla g 5 and Per a 5 (glutathione-S-transferases), Bla g 6 and Per a 6 (troponins), Bla g 7 and Per a 7 (tropomyosins), Bla g 8 (myosin light chain), Bla g 9 and Per a 9 (arginine kinases) and Per a 10 (serine protease) [5]. B. germanica enolase and vitellogenin have also been identified as novel cockroach allergens by proteomics approach [6]. In clinical practice, exclusive reactivity to either German or American cockroach extracts on skin testing is rarely observed among cockroach-allergic patients, and this is thought to be due to cross-reactivity to the homologous allergens.…”
Section: Introductionmentioning
confidence: 99%
“…The gel pieces were dehydrated with 100% ACN, dried, and subjected to in-gel digestion with sequencing-grade modified trypsin (enzyme-to-substrate ratio, 1:50; Promega) in 50 mM NH 4 HCO 3 overnight at 37°C. Peptides were extracted sequentially with 1% formic acid (FA), 60% ACN combined 0.1% FA and dried (25). To identify the protein modification by mass spectrometry (MS), tryptic-peptide preparation and data-dependent tandem MS (MS-MS) analysis were carried out as described previously (26).…”
Section: Methodsmentioning
confidence: 99%
“…Of note, only 1 of 28 African-American patients achieved an extended interval (Q4W) in this study. Long-interval darbepoetin regimens have also been studied extensively in patients not requiring dialysis (table 3) [101, 102]. …”
Section: Anemia Management In African-americans Through the Course Ofmentioning
confidence: 99%